THE INFLUENCE OF FINANCIAL SELF EFFICACY ON THE BEHAVIOR OF FINANCIAL MANAGEMENT OF MSMEs WITH FINANCIAL LITERACY AS A MODERATION VARIABLE - Ridha Ikbal, Ikhlasul; Hadady, Hartaty; Amiro, Suratno (Journal of Management and Islamic Finance, 2025)
This study aims to examine the effect of Financial Self-Efficacy on Financial Management Behavior of SMEs with Financial Literacy as a moderating variable. This research uses a quantitative approach and involves the population of Small and Micro Enterprises (SMEs) street vendors of agricultural produce in traditional markets in Central Ternate City, North Maluku Province. The sample in this study consists of 100 respondents. The data analysis technique used is Structural Equation Modeling (SEM) using statistical software Smart PLS 4. The results of this study indicate that: (1) Financial Self-Efficacy has a significant positive influence on Financial Management Behavior; (2) Financial Literacy acts as a moderating variable and can strengthen the effect of Financial Self-Efficacy on Financial Management Behavior in a positive and significant way. This study emphasizes that an increase in financial self-efficacy, supported by adequate financial literacy, can encourage more effective financial management behavior among SME actors.